1994
DOI: 10.2337/diacare.17.8.810
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-IV Levels and Phenotype Distribution in NIDDM

Abstract: Plasma apoA-IV levels are increased in NIDDM patients. This increase in apoA-IV is related mainly to hypertriglyceridemia and, to a lesser extent, to HDL cholesterol level. The apoA-IV phenotype distribution is not different between NIDDM patients and nondiabetic control subjects. The potential protective lipid profile (characterized by increased HDL and HDL2 cholesterol levels) linked with apoA-IV-1-2 phenotype in control subjects is no longer found in NIDDM patients. We suggest that the metabolic state of NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…Interestingly, APOA-IV levels were significantly higher in T2DM patients before the diet as compared to controls, which was also found in earlier studies [37],[38]. In contrast to our study, some also showed higher APOA-IV levels in obese, non-diabetic mice and humans [39],[40], though others did not find an association between APOA-IV and BMI [41].…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, APOA-IV levels were significantly higher in T2DM patients before the diet as compared to controls, which was also found in earlier studies [37],[38]. In contrast to our study, some also showed higher APOA-IV levels in obese, non-diabetic mice and humans [39],[40], though others did not find an association between APOA-IV and BMI [41].…”
Section: Discussionsupporting
confidence: 74%
“…ApoA-IV exerts a strong anti-atherogenic effect [17] and has also been suggested to act as a satiety factor. Plasma apoA-IV is elevated in human type 2 diabetes and obesity and decreases during weight reduction [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The increased expression of APOA4 was found in chronic kidney disease (CKD) patients [21]. In previous studies, plasma APOA4 levels were increased in DM patients, especially in noninsulin-dependent diabetes mellitus (NIDDM) patients [22, 23].…”
Section: Resultsmentioning
confidence: 99%